Rare bird documentation form for Northern Goshawk at East River Valley Park, 1982 - Bennett, Richard S.et al (1982)
Rare bird documentation form for a Northern Goshawk at East River Valley Park at Ames in Story County, IA on November 3, 1982. Epson - sheet feed